2020
DOI: 10.1002/lno.11612
|View full text |Cite
|
Sign up to set email alerts
|

Otolith chemistry of Electrona antarctica suggests a potential population marker distinguishing the southern Kerguelen Plateau from the eastward‐flowing Antarctic Circumpolar Current

Abstract: Large submarine plateaus impede the eastward flow of the deep‐reaching Antarctic Circumpolar Current (ACC), and at the southern Kerguelen Plateau (SKP), the ACC flow is steered north through the Fawn Trough and south through the Princess Elizabeth Trough. During the Kerguelen Axis study, a regional‐scale ecosystem survey, oceanographic sampling showed the ACC water properties west of the SKP to be distinct from those over the SKP. Electrona antarctica, a dominant mesopelagic fish species, is associated with Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…List of all identified species in the literature review arranged by taxa with data from their confirmed distribution, estimated maximum lifespan (MLSP), analytical techniques used in their study and relevant citations Species name Linkowski (1987), Hulley et al (1989), , Greely et al (1999), Duan et al (2020), Zhu et al (2018Zhu et al ( , 2020…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…List of all identified species in the literature review arranged by taxa with data from their confirmed distribution, estimated maximum lifespan (MLSP), analytical techniques used in their study and relevant citations Species name Linkowski (1987), Hulley et al (1989), , Greely et al (1999), Duan et al (2020), Zhu et al (2018Zhu et al ( , 2020…”
Section: Tablementioning
confidence: 99%
“…MgCa −1 and SrCa −1 ) in E. antarctica otoliths between populations across the Antarctic Circumpolar Current (ACC) and the southern Kerguelen Plateau (SKP, Duan et al 2020). Elemental ratios showed a total differentiation between the two populations during early stages of life and differences in later stages in life possibly due to different feeding habits (Duan et al 2020).…”
Section: Teleost Fishmentioning
confidence: 99%